Characteristics of the Sharia Supervisory Board, Sharia Company Size, Zakah, and Islamic Social Reporting on Sharia Banks in Indonesia - Rahmawan Arifin; Samsul Rosadi; Arif Nugroho; Tri Wahyuningsih (Falah: Jurnal Ekonomi Syariah, 2021)
This study aims to determine the effect of the characteristics of the Sharia Supervisory Board as proxied by the size of the sharia supervisory board, concurrent positions of the sharia supervisory board, sharia supervisory board meetings, company size, and Zakah on Islamic Social Reporting. Employing quantitative method, this study used panel data of Islamic commercial banks in Indonesia from 2015 to 2019. The data were analyzed using multiple linear regression by employing EViews 9 softwere. The result found that the variable of the size of the sharia supervisory board, concurrent positions of the sharia supervisory board, and the company size have a significant positive effect on Islamic Social Reporting. Meanwhile, sharia supervisory board meetings and Zakah have no effect on Islamic Social Reporting. The results of this study contribute to enriching the discourse of Islamic social reporting of sharia commercial banks in Indonesia, especially in terms of zakah and sharia supervisory characteristics.